2005
DOI: 10.1371/journal.pmed.0020097
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology and the Developing World

Abstract: How nanotechnology can be harnessed to address some of the world's most critical development problems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
124
0
12

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(136 citation statements)
references
References 4 publications
0
124
0
12
Order By: Relevance
“…The concerns about the negative impacts of nanotechnology on marginalized communities, voiced most cogently by the ETC Group (2003), are countered by others who point out that nanotechnology applications can become the means to achieve the United Nations Millennium Development Goals (see, for example, Salamanca-Buentello et al, 2005;United Nations Millennium Project, 2005). Thus, the United Nations Millennium Project report (ibid.)…”
Section: Global Equity and Rights : Implications For Developing Countmentioning
confidence: 99%
See 1 more Smart Citation
“…The concerns about the negative impacts of nanotechnology on marginalized communities, voiced most cogently by the ETC Group (2003), are countered by others who point out that nanotechnology applications can become the means to achieve the United Nations Millennium Development Goals (see, for example, Salamanca-Buentello et al, 2005;United Nations Millennium Project, 2005). Thus, the United Nations Millennium Project report (ibid.)…”
Section: Global Equity and Rights : Implications For Developing Countmentioning
confidence: 99%
“…Indeed, it is precisely such imperatives that drive the global pharmaceutical industry resulting in a focus on producing innumerable over-the-counter products for wealthier nations rather than ensuring access to essential, life-saving drugs for poorer ones. Recognizing the potential for nanotechnology to create winners and losers in both national and international contexts, scholars such as Baird and Vogt (2004) ask whether nanotechnology will address the most urgent problems of developing countries (energy, clean water, food) or just accept a 'global nanodivide' as we have come to live with a 'digital and genetic divide' (p393).The concerns about the negative impacts of nanotechnology on marginalized communities, voiced most cogently by the ETC Group (2003), are countered by others who point out that nanotechnology applications can become the means to achieve the United Nations Millennium Development Goals (see, for example, Salamanca-Buentello et al, 2005; United Nations Millennium Project, 2005). Thus, the United Nations Millennium Project report (ibid.)…”
mentioning
confidence: 99%
“…O Departamento de C&T da Índia anunciou investimentos de U$ 20 milhões no período de 2004-2009. Tailândia, Filipinas, Chile, México e Argentina também já têm programas de investimento em N&N 8 . Nesse contexto, merece destaque, uma excelente proposta voltada para a criação do Instituto de Nanotecnologia Brasil-Argentina, que resultou do proveitoso encontro das sociedades científicas dos dois países, no final de 2004.…”
Section: A Nanotecnologia E O Mundo Em Desenvolvimentounclassified
“…In 2005, the United Nations (UN) Millennium Project's Taskforce on Science, Technology and Innovation concluded that nanotechnology can contribute to the attainment of the Millennium Development Goals (MDGs), specifically, the goals to reduce child mortality, improve maternal mortality and combat HIV/AIDS, malaria and other diseases. [2,11,14] Health, specifically improved primary healthcare, is one of six focus areas highlighted in SA's National Nanotechnology Strategy (NNS), where nanotechnology can offer the most signi ficant benefits for the country. [15] Nanotechnology has a significant range of potential biomedical applications and is being used to develop nanodevices and structures to prevent, treat and monitor diseases.…”
mentioning
confidence: 99%